Analisis Implementasi Kebijakan Pemerintah Guna Meningkatkan Minat Beli Gen Z Terhadap Kain Endek Produksi Lokal Bali - Pramawati, I Dewa Ayu Agung Tantri; Putri, Kompiang Martina Dinata; Ratnaningrum, Luh Putu Rara Ayu (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2024)
Bali's Endek fabric is a type of traditional cloth from the island of Bali that holds high aesthetic value. This fabric is made using traditional weaving techniques in Bali. The government supports the preservation of local culture and increases purchase interest to help local Bali Endek fabric artisans through policies mandating the use of Endek fabric for work attire. However, Gen Z tends to be more interested in trendy, modern products connected to global trends. This study aims to analyze the implementation of government policies in increasing the purchase interest (Gen Z) towards locally produced Bali Endek fabric. The study takes place at INSTIKI among students who are already working. The research was conducted over approximately eight months. This study uses a descriptive qualitative research type. Descriptive qualitative methods align the opinions of the researcher with those of the informants. The researcher collects detailed data through observation, surveys, and documentation. The results of this study indicate that knowledge and perception of Endek fabric are quite high, driven by social media as the primary source of information. Government policies and promotions have a significant impact on the price and motivation to purchase Endek fabric. However, price, quality, and design remain the main considerations in the decision to buy Endek fabric.